The effects of social ties on rural-urban migrants' intention to settle in cities in China. (31st December 2018) - Huang, Xu; Liu, Ye; Xue, Desheng; Li, Zhigang; Shi, Zhilei
Abstract: The rapid increase of temporary migrants in large Chinese cities has led to the need for a nuanced and comprehensive understanding of the factors contributing to the influx. However, previous investigation into this subject has been undermined by an oversimplification of the concepts and measurements related to settlement intentions and migrants' social network. This study uses a combination of data from a 2013 nationwide survey and multilevel logit regressions to investigate the settlement intentions of 12, 807 rural-urban migrants across eight cities in China. It especially focuses on the ways in which social ties between migrants and people in their destination cities shaped their intention to settle there. This study makes an innovative contribution to the literature in three ways. First, it distinguishes between migrants' ties to non-residents (other migrants from the same place of origin), kin residents (local residents who are kin), and non-kin residents (local residents who are not kin). Second, it distinguishes between interactive social ties and supportive social ties. Third, it uses multiple indicators to measure the intention of migrants who decide to permanently settle, as well as hukou transfer and housing ownership. Findings from our analysis indicate that the newly formed intergroup ties of migrants and their existing intragroup ties exert different impacts on their intention to settle. Specifically, migrants' newly formed ties with non-kin residents are positively linked to their settlement intention, while their ties to non-residents are negatively associated with their settlement intention. Our findings also indicate that the social ties of migrants have different effects on the different dimensions of their settlement intention. The social ties of migrants play an important role in their permanent settlement and housing ownership intentions, but their effect on hukou transfer intentions is relatively weak. Additionally, our research discovered that supportive social ties play a more important role than do interactive social ties in shaping migrants' settlement intention. Highlights: Rural migrants who retain kin-based and home-based ties with other migrants in destination cities tend to have a weaker intention to settle in cities. Rural migrants who maintain kin-based ties with local residents or actively construct social ties with non-kin local residents tend to have a stronger intention to settle in cities. Compared to interactive social ties, supportive social ties play a more significant role in influencing migrants' settlement intention. Rural migrants' social ties play different roles in different patterns with regard to settlement intention.